Two novel phenanthraquinones with anti-cancer activity isolated from Bletilla striata. Issue 9 (1st May 2016) - Sun, Aijing; Liu, Jieqing; Pang, Suqiu; Lin, Junsheng; Xu, Ruian
Graphical abstract: Abstract: 7-Hydroxy-2-methoxy-phenanthrene-3, 4-dione and 3′, 7′, 7-trihydroxy-2, 2′, 4′-trimethoxy-[1, 8′-biphenanthrene]-3, 4-dione, two novel compounds and four known compounds were isolated from Bletilla striata . The structures of the compounds were established on the basis of extensive spectroscopic analysis. The two compounds exhibited antiproliferative effects using the MTT test; these effects may be due to cell cycle arrest and inducing ROS generation.